Neural correlates of acute apraxia: Evidence from lesion data and functional MRI in stroke patients. (November 2019) - Dressing, Andrea; Kaller, Christoph P.; Nitschke, Kai; Beume, Lena-Alexandra; Kuemmerer, Dorothee; Schmidt, Charlotte S.M.; Bormann, Tobias; Umarova, Roza M.; Egger, Karl; Rijntjes, Michel; Weiller, Cornelius; Martin, Markus
Abstract: Behavioral deficits after stroke like apraxia can be related to structural lesions and to a functional state of the underlying network – three factors, reciprocally influencing each other. Combining lesion data, behavioral performance and passive functional activation of the network-of-interest, this study aims to disentangle those mutual influences and to identify 1) activation patterns associated with the presence or absence of acute apraxia in tool-associated actions and 2) the specific impact of lesion location on those activation patterns. Brain activity of 48 patients (63.31 ± 13.68 years, 35 male) was assessed in a fMRI paradigm with observation of tool-related actions during the acute phase after first-ever left-hemispheric stroke (4.83 ± 2.04 days). Behavioral assessment of apraxia in tool-related tasks was obtained independently. Brain activation was compared between patients versus healthy controls and between patient with versus without apraxia. Interaction effects of lesion location (frontal vs parietal) and behavioral performance (apraxia vs no apraxia) were assessed in a 2 × 2 factorial design. Action observation activated the ventro-dorsal parts of the network for cognitive motor function; activation was globally downregulated after stroke. Apraxic compared to non-apraxic patients showed relatively increased activity in bilateral posterior middle temporal gyrus and middle frontal gyrus/superior frontal sulcus. Altered activation occurred in regions for tool-related cognition, corroborating known functions of the ventro-dorsal and ventral streams for praxis, and comprised domain-general areas, functionally related to cognitive control. The interaction analyses revealed different levels of activation in the left anterior middle temporal gyrus in the ventral stream in apraxic patients with frontal compared to parietal lesions, suggesting a modulation of network activation in relation to behavioral performance and lesion location as separate factors. By detecting apraxia-specific activation patterns modulated by lesion location, this study underlines the necessity to combine structural lesion information, behavioral parameters and functional activation to comprehensively examine cognitive functions in acute stroke patients.